PENGARUH E-SERVICE QUALITY TERHADAP E-CUSTOMER LOYALTY MELALUI E-SATIFCATION SEBAGAI MEDIATOR DALAM E-WALLET INDONESIA - Efdison, Zefri; Lova, Anggil Nopra; Y, Yelnim; Liantifa, Melifia (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
This research aims to determine the effect of e-service quality on e-customer loyalty mediated by e-satisfaction among e-wallet users in Indonesia. The sample of this research was 100 respondents. Data was collected using a questionnaire that has been tested for validity and reliability. The data analysis technique used is descriptive analysis using SEM Amos 22. The results of the research show that there is a significant direct influence between e-service quality on e-satisfaction and e-customer loyalty among e-wallet users. There is a partial influence of the mediating impact of e-satisfaction between e-service quality on e-satisfaction and e-customer loyalty on e-wallet users. This shows that customer satisfaction can be built through good service so that customers do not switch to competitors.